Epidemiological characteristics of bicycle-related injuries with the emergence of the covid-19 - Ko, B. S.; Cho, S. H.; Noh, D. Y.; Kim, J. G. (The Korean Journal of Sports Medicine, 2021)
Purpose: Following the outbreak and global spread of the coronavirus disease 2019 (COVID-19), an increasing number of people have turned to cycling. This study aims to investigate the epidemiology of bicycle-related injuries before and after the emergence of the COVID-19.